Safety Leadership Culture and Employee Behavior in Cement Plant Group Operations - Slamet Widodo (International Journal Labs, 2026)
Given the high level of risk in the cement industry, occupational safety is an important component. The purpose of this study was to investigate how employee behavior at the Tuban Group Operation is influenced by safety leadership culture. Interviews were conducted with several employees who had different responsibilities within one unit, and the data were collected using a qualitative approach with thematic analysis supported by NVivo 12 Pro software. The findings of the study indicate that two main factors—internal factors consisting of commitment, communication, coordination, attention, and leaders’ role modeling, and external factors consisting of compliance with standard operating procedures (SOPs), company policies, and safety golden rules—have a significant impact on employee perceptions of the safety culture built by leaders at the Semen Group Operation Tuban factory. Both factors encourage safe behavior in the workplace, increase employee awareness, and create a positive safety climate. This study can serve as a guide for creating a sustainable and comprehensive safety-oriented workplace culture that supports the development of a more effective safety leadership approach.